Tamarillo Juice (Solanum betaceum Cav) as An Alternative to Increase Hemoglobin Levels for Pregnant Women with Anemia - Juana Linda Simbolon; Emilia Silvana Sitompul (Babali Health, 2021)
Introduction: World Health Organizations recommends pregnant women to consume 120-240 mg of iron (in the form of Ferrum) per day and increase the dose by 400 mg 3 times a day if the Anemia is severe. One of the herbal therapies that can increase hemoglobin levels is Tamarillo (Solanum Betacum Cav) with a vitamin C level of 25 mg, Fe 2,765 ppm. The research objective was to analyze the effect of Tamarillo juice consumption in increasing hemoglobin (HB) levels of pregnant women with Anemia. Methods: Quasi-experimental research with pre and post-test along with control group design was used to compare the HB levels of ≥ 32 weeks pregnant women who were given Tamarillo fruit juice. Subjects in this study were 34 pregnant women as the treatment group who received Tamarillo juice and blood supplement and the control group of pregnant women who only receive blood supplements. Results: The results of the T-test analysis showed that in the treatment group there was an increase in the average hemoglobin level of 0.91 g/dL in the first week and 1.75 g/dL in the second week, while in the control group there was an increase in the average hemoglobin level of 0.43 g/dL in the first week and an increase of 0.89 g/dL in the second week. Conclusion: The administration of Tamarillo juice as an alternative companion to blood supplement in the prevention and management of care for pregnant women with Anemia.